Analisis Karakteristik, Perilaku, dan Motivasi Perjalanan Wisatawan Asal Sulawesi Utara ke Jakarta - Ade Suherlan (Esensi: Jurnal Bisnis dan Manajemen, 2014)
This study aims to analyze the characteristics, behaviors and motivations of tourists from North Sulawesi trip to Jakarta. The research methodology used is descriptive qualitative method. The data used is primary data and secondary data collection method through survey questionnaires, interviews, and focus group discussion.  Data analysis used SPSS statistical analysis includes frequency and cross-tab analysis, and SWOT analysis. The results of this study of which are domestic tourists from North Sulawesi classified as "Upper Market" and prestigious tourist fond of, and impressed consumptive, hedonist, shopping, parties and meals. Travelers from North Sulawesi like to go to some of the famous tourist destinations. Travelers from North Sulawesi more confident when to travel alone in the country. The main obstacle is the lack of information about Jakarta especially for the people of North Sulawesi, unavailability of brochures about Jakarta in service, not available tourist maps. Information about the attractions that can be visited very minimal and should be provided free of charge such as tourist information facilities at the airport, in the center of the crowd, tourist destination, and so on. Packaging destination must be continuously improved; Jakarta is highly prestigious for the people of North Sulawesi.DOI: 10.15408/ess.v4i3.2432